Pemilihan dan Pemanfaatan Pengembangan Bahan Ajar Mata Pelajaran IPS dan PPKN pada Pendidikan Dasar - Muhammad Ikmal Faizi (Jurnal Ilmiah Madrasah, 2024)
AbstractThis research was conducted with the aim of identifying and obtaining information about the selection and use of developing teaching materials for social studies and PPKN subjects in basic education. This research uses the library research method, which is a data collection method by studying theories from various literature sources that are related to this research. This research provides an explanation of the criteria for selecting and utilizing the development of social studies and PPKN teaching materials in basic education. There is no success of a teacher in developing teaching materials without support from the school and his own competence. It is important for school principals to improve teacher competency in order to create an effective and enjoyable learning atmosphere so that students feel comfortable learning and can achieve educational goals.Keywords: Development of Teaching Materials, Social Sciences and PPKN, Basic Education AbstrakPenelitian ini dilaksanakan bertujuan untuk mendapatkan informasi tentang Pemilihan dan Pemanfaatan Pengembangan Bahan Ajar Mata Pelajaran IPS dan PPKN Pada Pendidikan Dasar. Penelitian ini menerapkan metode studi Pustaka (Library Research), yang merupakan suatu metode yang mencari dan melakukan pengumpulan data dengan mempelajari dasar teori dari berbagai referensi literatur yang memiliki keterhubungan dengan penelitian ini. Proses penelitian ini memberikan penjelasan tentang kriteria pemilihan dan pemanfaatan pengembangan bahan ajar IPS dan PPKN pada Pendidikan Dasar. Tidak adanya keberhasilan seorang guru dalam pengembangan bahan ajar tanpa dukungan oleh pihak sekolah dan kompetensi dirinya. Penting bagi kepala sekolah guna menunjang kompetensi guru sebagai upaya untuk menyelenggarakan dan mewujudkan suasana belajar yang nyaman serta efisien dan bermakna sehingga peserta didik merasa nyaman untuk belajar serta dapat tercapai tujuan Pendidikan.Keywords: Pengembangan Bahan Ajar, IPS dan PPKN, Pendidikan Dasar